Sintaxe e suas interfaces - Ibaños, Ana Maria Tramunt; Othero, Gabriel de Ávila; Biasibetti, Ana Paula Correa da Silva (Letrônica, 2015)
Apresentação do Dossiê de Linguística: Sintaxe e suas interfaces